1982
DOI: 10.1515/jpme.1982.10.6.273
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum extraction and neonatal jaundice

Abstract: Various fetal scalp lesions are related to the use of the vacuum extractor. Blood sequestered in these lesions could result in an increased bilirubin load on the functionally limited neonatal liver, leading to the development of hyperbilirubinemia. In the present study bilirubin levels of vacuum extracted neonates were compared with those of non-instrumentally delivered babies during the first 72 hours of life. Sixty-nine vacuum extracted neonates had higher bilirubin levels than 56 non-instrumentally delivere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Study done by Arad I et al and Banu F et al showed that there was no significant difference in gestational age between the two groups. 5,6 In the present study, there was no significant difference in gestational age between manual and forceps extraction groups (P=0.42), between forceps and vacuum extraction groups (P=0.43) and between manual and vacuum extraction groups (P=0.42) ( Table 4).…”
Section: Resultsmentioning
confidence: 46%
See 1 more Smart Citation
“…Study done by Arad I et al and Banu F et al showed that there was no significant difference in gestational age between the two groups. 5,6 In the present study, there was no significant difference in gestational age between manual and forceps extraction groups (P=0.42), between forceps and vacuum extraction groups (P=0.43) and between manual and vacuum extraction groups (P=0.42) ( Table 4).…”
Section: Resultsmentioning
confidence: 46%
“…In the study done by Arad I et al the U-D interval in the manual extraction group was 40.9±9.8 seconds and in the Vacuum extraction group it was 79.4±10.2 seconds. 5 Sritippayawan S et al found the U -D interval in the manual extraction and vacuum extraction group to be 86.3±53.9 seconds and 65.3±31.2 seconds respectively. 2 The U-D interval in the manual and vacuum extraction group was 43.5±8.6 seconds and 75.6±9.02 seconds respectively, in the study done by Banu F et al 6 The difference in U-D interval was found to be significant in the studies done by Arad I et al (P<0.01), Sritippayawan, S et al (P<0.001) and Banu F et al (P≤0.0001).…”
Section: Resultsmentioning
confidence: 96%
“…She had to be admitted to the special care baby unit. Three other neonates in the complaints group also had to be admitted to the special care baby unit due to feeding difficulties (2) or hyperbilirubinemia that required phototherapy (1). All vacuum extraction-related complaints occurred within the first 7-10 h following birth (see Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Hyperbilirubinemia requiring phototherapy has been observed more often after vacuum extraction than after spontaneous delivery [2,4,15]. Hyperbilirubinemia following vacuum extraction might be associated with resorption of head skin and cephalic hematoma that have been described in vacuum-delivered neonates [12,18,19,[23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%